PENGARUH KOMITMEN PROFESIONAL, SOSIALISASI ANTISIPATIF DAN LOCUS OF CONTROL TERHADAP WHISTLEBLOWING INTENTION: (Studi Kasus Pada SKPD Pemerintah Daerah Kabupaten Flores Timur) - Plue, Theresia Dawan; Soleiman, Iriany Dewi; Sayang, Sabulon (Program Studi Akuntansi Universitas Flores, 2020)
The purpose of this study was to determine (1) the effect of professional commitment on whistleblowing intention. (2) the effect of anticipatory socialization on whistleblowing intention. (3) the effect of locus of control on whistleblowing intention. This type of research is quantitative research. The data analysis used is descriptive quantitative to measure the influence of professional commitment, anticipatory socialization and locus of control on whistleblowing intention with the help of the Statistical Package for the Social Sciens (SPSS) program for windows. The results of this study indicate (1) Professional Commitment has a significant effect on Whistleblowing Intention in the Regional Government SKPD of East Flores Regency. This result is evidenced by the coefficient value of the Professional Commitment variable of 0.297 with tcount> ttable (2.354> 1.672) and a significant level of 0.022 <0.05. (2) Anticipatory Socialization has a significant effect on Whistleblowing Intention in the Regional Government SKPD of East Flores Regency. This result is evidenced by the coefficient value of the Anticipatory Socialization variable of 0.289 with tcount> ttable (2.195> 1.672) and a significant level of 0.033 <0.05. (3) Locus of Control has a significant effect on Whistleblowing Intention in the Regional Government SKPD of East Flores Regency. These results are evidenced by the value of the coefficient of the Locus of Control variable of 0.236 with tcount> ttable (2.105> 1.672) and a significant level of 0.040 <0.05.